Psikologi Pendidikan dalam Meningkatkan Motivasi Belajar Siswa - Saskia Dwi Agnesia; Ellen Prima (INDO PUBLISHING, 2026)
Educational psychology is a branch of psychology that studies individual behavior in the learning process. In the field of education, learning motivation is an important factor that influences students' success in achieving learning goals. Low learning motivation can lead to decreased academic achievement, lack of student participation in learning activities, and low interest in learning. This article aims to discuss the role of educational psychology in improving students' learning motivation through psychological approaches carried out by teachers, families, and the school environment. The method used in this article is a literature study by reviewing various journals, books, and relevant scientific sources. The results of the discussion indicate that educational psychology has an important role in understanding students' characteristics, learning needs, interests, talents, and emotional conditions. Through the implementation of appropriate learning strategies, rewards, social support, and a conducive learning environment, students' learning motivation can be significantly improved.